Prácticas de enseñanza de lógica-matemática en inicial 2 en el Centro Infantil La Salle. - Cadena Caiza, Carla Azucena (2016)
This paper discusses the mathematical logic-Initial Education in Educational Practices. Its main objective was to understand and analyze the pedagogical practice in education. The variables used for the research were: methodological structure, planning, assessment strategies, interaction between teacher-student and academic tasks. In addition, we sought to know how the teacher has all these elements and how they interact with each other so that the process of teaching and learning that occurs in this area. At the same time practice leads teachers to reflect on how it contributes to the formation of student learning, in this case in the field, logical-mathematical that is important in human life, because this inverse in each situation it presented and provides insight into the surrounding environment and troubleshooting. The focus of this research was based on the qualitative method because cutting is interpretive, it helps to understand the phenomenon under study, work took two forms: literature and field research. The observation and interview techniques were also used and the instruments used were: field diary and observation sheet, which provided for the collection and interpretation of data. The results obtained allowed to understand how the teacher conducted the-mathematical logic and how the various elements used in practice contributed to this learning area of pedagogical practice.